BEBERAPA FAKTOR PENYEBAB GANGGUAN FAAL PARU PADA PENJUAL UNGGAS DI PASAR BURUNG KUPANG SURABAYA - Fariz Zuvil Arganata (The Indonesian Journal of Occupational Safety and Health, 2016)
Poultry sellers is one of the jobs potentially impaired pulmonary function. Impaired pulmonary function status of workers caused by external factors and internal factors. The aim of this research was to identify factors which cause impaired pulmonary function the poultry sellers in bird market in Kupang Surabaya. This research used cross sectional design. Data obtained by the measurements, examination and questionnaire. The sample of this research is 20 respondents which drawn from 10% of the total population. Data were analyzed by cross tabulation. The measurements result of dust levels, SO2, NO2, NH3 and H2S respectively 0.3848 mg/m3, 0.0047 mg/m3, 0.0207 ppm, 0.0638 ppm, 0.0002 ppm were below the TLV. Pulmonary function test results of 20 respondents, there were 13 (65%) of respondents have normal status of pulmonary function and 7 (35%) of respondents impaired pulmonary function with details of 4 (20%) of respondents mild obstruction, 1 (5%) of respondents restriction mild and 2 (10%) of respondents mixture. The conclusion of this study are the pulmonary status of respondents in Surabaya Kupang bird market not affected by external factors such as exposure to gas and dust, but affected by internal factors such as age, years of service, and years of smoking history. There is no association between the nutritional status of respondents with pulmonary function status. Respondents should reduce cigarette consumption and conduct regular health checks.Keywords: pulmonary function status, sellers poultry, bird market